PENGARUH ENVIRONMENTAL SOCIAL AND GOVERNANCE, SALES GROWTH, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP TAX AVOIDANCE: TAX AVOIDANCE - Erika Monalisa (JEKOS (Jurnal Ekonomi Dan Sosial), 2024)
This study aims to determine the influence of ESG, sales growth and institutional ownership on tax avoidance in Non-cyclical Food & Beverage Sector Consumer Non-cyclical Companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The population in this study is 62 companies. This study uses 8 companies selected using the purposive sampling method from the 2018–2022 period with a sample size of 40 data. The data used is quantitative data sourced from secondary data, then the collected data is tested and analyzed Research data processing analysis using Eviews 12. Based on the results of the study, it shows that simultaneously ESG, sales growth and institutional ownership have an effect on tax avoidance.   Keywords : ESG, Sales Growth, Institutional Ownership, Tax Avoidance